Strategi guru pendidikan agama islam dalam menanamkan nilai toleransi di sekolah - Aisy, Salwatul (Maliki Interdisciplinary Journal, 2025)
This article discusses tolerance, an important value in social life that aligns with Islamic teachings on tolerance, or mutual respect for differences. In the context of Islamic Religious Education (PAI), the value of tolerance is taught not only through theory but also through concrete practices in learning. Teachers play a key role in instilling this attitude, whether through advice, providing an understanding of differences, role models, or collaborative learning methods such as group discussions. However, implementing tolerance in schools is not without challenges, such as the influence of a less inclusive external environment, limited teaching materials, and differences in values ​​between schools and families. To overcome these obstacles, PAI teachers implement more varied strategies, such as dialogue with parents, story- and experience-based learning methods, and the development of extracurricular activities. Through collaboration between schools, families, and the community, the value of tolerance can be instilled more effectively, enabling students to grow into individuals with morals, openness, and prepared to live in harmony amidst diversity.